EFEKTIVITAS FOOT HYDROTERAPI DENGAN CAMPURAN GARAM DAN JAHE TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI DESA SIHOTANG HASUGIAN TONGA - Marlina Marlina; Hizkianta Sembiring (Universitas Murni Teguh, 2026)
Hypertension is a common non-communicable disease and a major risk factor for various complications such as stroke, heart failure, and kidney disease. One of these is complementary foot hydrotherapy with a mixture of salt and ginger, which works through vasodilation, increased peripheral circulation, a relaxing effect, and decreased sympathetic nerve activity. This study aims to determine the effectiveness of foot hydrotherapy with a mixture of salt and ginger on reducing blood pressure in hypertension patients in Sihotang Hasugian Village, Tonga. This research methode is a quantitative approach, analytical pre-experimental research design in one group pre-post-test design approach. The number of respondents as many as 20 people was selected using a purposive sampling technique, Data analysis was carried out using the Wilcoxon Signed Rank Test. The results of this study with the Wilcoxon test showed a p value = 0.000 (p <0.05), which means there is a significant difference between blood pressure before and after the intervention. indicating a significant effect of Foot Hydrotherapy with a Mixture of Salt and Ginger on Reducing Blood Pressure in Hypertension Patients. The Conclusion of this Foot Hydrotherapy with a mixture of salt and ginger is effective in lowering blood pressure in hypertension sufferers and can be applied as a non-pharmacological therapy in the management of hypertension in health facilities.